Validating the testing of solar air collectors under simulated radiation - San Mateo, Jesus Amado A.
This thesis seeks to validate the use of indoor testing of solar air collectors under simulated solar radiation. By conducting performance tests under a solar simulator and comparing the results with those obtained from outdoor testing, the accuracy of indoor testing can be determined. Since most of the established and accepted test procedures are designed for outdoor testing under clear sky conditions in temperature climates, the ability to conduct tests indoors eliminates the variability in weather conditions, a serious problem in conducting tests in the Philippines.